CHANGE MANAGEMENT DALAM MENGHADAPI PERSAINGAN BISNIS KONSULTAN PENGEMBANGAN SDM - Giri Susilo Hadi Joko Purnomo; warsino . (JURNAL GAUNG INFORMATIKA, 2017)
Human Resources (HR) is an important component in a company, so a massive and continuous effort is needed in managing HR in a company. As the change in theparadigm of HR management in a company causes the level of competition in the world of HR development consulting business in Indonesia is very tight. Consultant companies that cannot adapt to these changes will automatically be overwhelmed by existing developments. Change is a transformation from the present state to the expected condition in the future, a better condition of course. Change is a sign in life that always takes place constantly. Only companies that have the ability to adapt to change will be able to survive. Change management is one of the important strategies of a company capable of increasing competitiveness. Change management that involves intense relationships between employees and management will boost a company's competitive advantage. The research method uses a qualitative approach through collecting change management literature. Competition in the business world of consultants increasingly demands the improvement of the quality and innovation of personnel and products continuously and consistantly.